Microula roseiflora (Boraginaceae), a new species from Qinghai-Tibetan Plateau - Yu, Wen-Tao; Yu, Yun; Shen, Jian-Guo; Guo, Qiong-Xia (Phytotaxa, 2016)
In this paper, we describe and illustrate Microula roseiflora as a new species from Qinghai-Tibetan Plateau. The new species is morphologically similar to M. muliensis and M. leiocarpa, but M. roseiflora can be easily distinguished by the combination of characteristics: nutlet black spotted; dorsal pseudoaperture ca. 0.5 mm long; corolla pink; faucal appendages triangular-ovate; upper stem leaf elliptic to ovate; and stem trichomes appressed, ca. 0.3–1.5 mm long. For the new taxon, information on its geographic range, habitat and hypothetical taxonomic affinities is provided.